2008
DOI: 10.1073/pnas.0712231105
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale model of mammalian thalamocortical systems

Abstract: The understanding of the structural and dynamic complexity of mammalian brains is greatly facilitated by computer simulations. We present here a detailed large-scale thalamocortical model based on experimental measures in several mammalian species. The model spans three anatomical scales. (i) It is based on global (white-matter) thalamocortical anatomy obtained by means of diffusion tensor imaging (DTI) of a human brain. (ii) It includes multiple thalamic nuclei and six-layered cortical microcircuitry based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
758
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 913 publications
(774 citation statements)
references
References 37 publications
9
758
1
6
Order By: Relevance
“…Towards this objective, a number of computational studies have attempted to combine interregional connectivity data with intra-regional circuit and cellular properties to produce large-scale models of cortical (Ghosh et al, 2008;Honey et al, 2007Honey et al, , 2009Knock et al, 2009) and corticothalamic function (Izhikevich and Edelman, 2008). The value of modeling studies is twofold.…”
Section: Functional Connectomicsmentioning
confidence: 99%
“…Towards this objective, a number of computational studies have attempted to combine interregional connectivity data with intra-regional circuit and cellular properties to produce large-scale models of cortical (Ghosh et al, 2008;Honey et al, 2007Honey et al, , 2009Knock et al, 2009) and corticothalamic function (Izhikevich and Edelman, 2008). The value of modeling studies is twofold.…”
Section: Functional Connectomicsmentioning
confidence: 99%
“…The dynamics of each neuron in the network is modelled as described by Izhikevich & Edelman (2008). Depending on the values of the parameters a, b, c and d, this model reproduces the spiking dynamics of each of the three neuronal types: RS, FS and LTS (Izhikevich & Edelman 2008).…”
Section: Model Dynamicsmentioning
confidence: 99%
“…Depending on the values of the parameters a, b, c and d, this model reproduces the spiking dynamics of each of the three neuronal types: RS, FS and LTS (Izhikevich & Edelman 2008). The values of a, b, c, d, v r , v t , v peak , C and k used in this study are shown in Table 1.…”
Section: Model Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations